ANALISIS PERBANDINGAN KEPUASAN NASABAH BANK RAKYAT INDONESIA SEBELUM DAN SETELAH PEMBERLAKUKAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) - Tagor Rambey; Ahmad Nurdin Hasibuan (Jurnal Manajemen dan Bisnis, 2021)
This study aims to analyze the comparison of customer satisfaction at BRI KCP Unit Lenteng Agung before and after PPKM which is influenced by service quality and product quality. The research location was chosen by BRI KCP Lenteng Agung unit. Furthermore, the technique of determining the sample using non-probability techniques in the type of accidental / convinient sampling type of purposive judgment sampling. The method used is purposive sampling with the criteria of 1) BRI Lenteng Agung customers, 2) customers who have completed transactions at BRI Lenteng Agung, 3) carried out during PKKM. Samples from customers were taken as many as 100 people. According to the value of Sig. (2-tailed) then there is no difference between the average value of service quality before and during the pandemic. There is a relationship between service quality before and after the pandemic is very close and significant. There is no difference between the average product quality scores before and during the pandemic. However, there is a very close and significant relationship between product quality before and after the pandemic. There is no difference between the average value of customer satisfaction before and during the pandemic, and there is a very close and significant relationship between customer satisfaction before and after the pandemic.